Chemically delaminated free standing covalent organic nanosheets (CONs) - Khayum, Abdul M.; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; porous polymers; ultra thin nano sheets

Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

Covalent organic framework thin-films for molecular separation - Dey, Kaushik; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Separation; Thin-films

Crystalline porous materials for gas adsorption - Pal, Tapan Kumar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; gas adsorption

Decoding the morphological diversity in two dimensional crystalline porous polymers - Halder, Arjun; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Density functional calculations; Morphology

Supramolecular reassembly of self-exfoliated ionic covalent organic nanosheets for label-free detection of double-stranded DNA - Mal, Arindam; Mishra, Rakesh K.; Praveen, Vakayil K.; Khayum, M. Abdul; Banerjee, Rahul; Ajayaghosh, Ayyappanpillai (Angewandte Chemie-International Edition, 2018)
Ionic covalent organic nanosheets (iCONs), a member of the two-dimensional (2D) nanomaterials family, offer a unique functional platform for a wide range of applications. Herein, we explore the potential of an ethidium bromide (EB)-based covalent organic framework (EB-TFP) that self-exfoliates in water resulting in 2D ionic covalent organic nanosheets (EB-TFP-iCONs) for the selective detection of double-stranded DNA (dsDNA). In an aqueous medium, the self-exfoliated EB-TFP-iCONs reassemble in the presence of dsDNA resulting in hybrid EB-TFP-iCONs-DNA crystalline nanosheets with enhanced fluorescence at 600 nm. Detailed steady-state and time-resolved emission studies revealed that the reassembly phenomenon was highly selective for dsDNA when compared to single-stranded DNA (ssDNA), which allowed us to use the EB-TFP-iCONs as a 2D fluorescent platform for the label-free detection of complementary DNA strands.
Keywords: Covalent organic framework; DNA; ionic assembly; ionic covalent organic nanosheets; label-free detection

Transforming covalent organic framework into thin-film composite membranes for hydrocarbon recovery - Biswal, Bishnu P. (Separation Science and Technology, 2018)
We, for the first time, employed chemically stable covalent organic framework (COF) (TpPa-1) as a transport-active phase within the polymer (styrene-butadiene rubber; SBR) matrix to make TpPa-1@SBR thin-film composite (TFC) membranes. Three composite membranes, viz., TpPa-1(30)@SBR, TpPa-1(50)@SBR, and TpPa-1(70)@SBR have been prepared with varying COF content. These membranes were characterized for gas permeance and results were compared with the pristine SBR-based TFC membrane. The fully organic nature of chemically stable COF offered good compatibility with the host polymer matrix (SBR) and resulted into flexible TFC membranes even at 70% of COF loading; compared to the other porous material (MOFs or Inorganic fillers), it is appreciable.
Keywords: Covalent organic framework; hydrocarbon recovery; propylene–propane; styrene-butadiene rubber; thin film composite

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

Nanoporous covalent organic framework embedded with Fe/Fe3O4 nanoparticles as air-stable low-density nanomagnets - Kushwaha, Rinku; Kaleeswaran, Dhananjayan; Haldar, Sattwick; Chakraborty, Debanjan; Mullangi, Dinesh; Borah, Aditya; Vinod, Chathakudath P.; Murugavel, Ramaswamy; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2020)
Covalent organic frameworks (COFs) made of light atoms such as H, C, N, and O with a significant void-to-framework ratio are excellent low-density supports for nanoparticles (nPs). Their framework can be precoded with heteroatoms to ensure binding with metallic nanoclusters. With these advantages, if controlled amounts of magnetic nPs are anchored to them, they can yield low-density organic-inorganic nanomagnets. Their organic nature facilitates fusion with bulk materials such as paper/textile to enable bulk composites with well-dispersed low-density magnets, which have potential for defense and next-generation aviation applications. Herein, we have grown small Fe/Fe3O4 nPs (5-18 wt %) inside a COF. Interestingly, 300 mg of this organic-inorganic framework material (containing 50 mg of nPs) can lift a vial of similar to 15,000 mg (300 times heavier). Also, the hydrophobic COF wraps around the Fe/Fe3O4 nanocluster retaining its room-temperature magnetic character even after 1 year, while the naked nPs lose it within a few days because of air oxidation. Bulk composites with paper and polymers have been made using this low-density Fe-COF to demonstrate their processability.
Keywords: air-stable nanomagnets; Covalent organic framework; Fe/Fe3O4 nanoparticles; low-density nanomagnets; magnetic rayon; nanoporous COF

Synergistic electronic effects in AuCo nanoparticles stabilized in a triazine-based covalent organic framework: a catalyst for methyl orange and methylene blue reduction - Devulapalli, Venkata Swaroopa Datta; Kushwaha, Rinku; Ovalle, Edwin; Singh, Himan Dev; Shekhar, Pragalbh; Chakraborty, Debanjan; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan; Borguet, Eric (ACS Applied Nano Materials, 2022)
Developing stable active catalysts for reducing water-soluble pollutants is a desirable target. In this pursuit, we have functionalized covalent organic frameworks (COFs) with gold (Au) and cobalt (Co) nanoparticles via a one-step aqueous synthesis process, and their catalytic activity in reducing methyl orange and methylene blue is examined. Operando absorbance measurements of methyl orange (anionic dye) reduction revealed AuCoCOF (1.3 Au/1.0 Co) to have superior kinetics over many other catalysts, which typically require additional external stimuli (e.g., photons) and higher catalyst loadings. After confirming the homogeneous dispersion of the nanoparticles on the COF support using three-dimensional (3D) tomography and material stability through powder X-ray diffraction (PXRD), infrared (IR), and thermal studies, we investigated their redox activity. Cyclic voltammetry (CV) confirmed the involvement of both metals in the redox process, while spectroelectrochemical measurements show that their activity and kinetics remain unaltered by an applied potential. Solid-state UV measurements reveal that the neat COF is a semiconductor with a large band gap (2.8 eV), which is substantially lowered when loaded with cobalt nanoparticles (2.2 eV for CoCOF). The electronic synergy between Au and Co nanoparticles further reduces the band gap of AuCoCOF (1.9 eV). Thus, there is a definite advantage in doping non-noble metal nanoparticles into a noble metal lattice and nanoconfining them into a porous COF support. Our study highlights the significance of bimetallic COF-supported nanocatalysts, wherein one can engage each component toward targeted applications that demand redox activity with favorable kinetics.
Keywords: AuCoCOF; band gaps; Covalent organic framework; methyl orange reduction; Nanoparticles; UV-vis spectroscopy